Numerical Simulation of the Effect of Long-Term Reclamation on the Flow and Sediment Concentration in Binhai Port,Yancheng - ZHU Siyu; LU Dan (Renmin Zhujiang)
Binhai Port is located at the most obvious corrosive coastline of the abandoned Yellow River delta in the north of Jiangsu Province,where the near-shore wave and flow dynamic is strong,the sediment movement is relatively active,the underwater terrain is complex and the slope erosion is obvious.Based on the measured hydrological and sediment data and a two-dimensional mathematical model for wave,tidal current and sediment,this paper quantitatively analyzes the influence of the long-term reclamation project on the flow and sediment concentration in the study area and the surrounding estuary,and emphatically discusses the back silting characteristics and deposition causes of the 300 000-ton channel during normal and rough weather.The results show that:After the implementation of the reclamation project,the flow and sediment characteristics of the study area don't change in a large scale,and mainly the flow and sediment near the project site is affected.The sediment is deposited after the channel dredging and a sediment deposit centered at the area with peak sediment concentration is formed in the channel,with decreasing deposition thickness to the port and outer sea channel.During rough weather,the maximum deposition thickness can reach 8~24 times of that in normal weather,but it is less than 0.2 m/d and there is no sudden silting and navigation blocking.